1994
DOI: 10.1159/000187791
|View full text |Cite
|
Sign up to set email alerts
|

Creatol, a Creatinine Metabolite, as a Useful Determinant of Renal Function

Abstract: Analysis of creatoi (CTL, 5-hydroxycreatinine), an oxidative creatinine (Cr) metabolite, in serum and urine of human subjects has indicated that CTL is a useful determinant of renal function. The existence itself of serum CTL (s-CTL) could be a diagnostic sign for chronic renal failure (CRF): in all normal subjects, s-CTL was undetectable, but s-CTL was detectable in sera of all patients with CRF (s-Cr: > 2.0 mg/dl). And the s-CTL values increased in proportion to the severity of CRF in such patients. Furtherm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 9 publications
3
16
0
Order By: Relevance
“…Daily severity of CKD. Both CTL and MG in serum and urine were initially indicated to be markers for CRF (1,(12)(13)(14). However, both were later recognized to be markers of •OH (1-3,5-9).…”
Section: Daily Amount Of •Oh Scavenged By Deoxyguanosine (Dg) and Crnmentioning
confidence: 99%
See 1 more Smart Citation
“…Daily severity of CKD. Both CTL and MG in serum and urine were initially indicated to be markers for CRF (1,(12)(13)(14). However, both were later recognized to be markers of •OH (1-3,5-9).…”
Section: Daily Amount Of •Oh Scavenged By Deoxyguanosine (Dg) and Crnmentioning
confidence: 99%
“…Although we can detect in vitro creatones A and B as intermediates from CTL to MG (11), we do not introduce them herein, because they are not detectable in vivo. CTL and MG in serum and urine have been recognized as in vivo markers of •OH (1-3,5-9), although they were initially known as markers for chronic renal failure (CRF) (12)(13)(14). We can estimate their daily scavenging capacity for •OH using the urinary Crn-related metabolites of CTL, MG, and DMC.…”
Section: Introductionmentioning
confidence: 99%
“…The molar ratio (CTL + MG)/Crn in serum and urine is correlated well with sCrn values (1,50,58). It was thought that sMG increases in proportion to sCrn according to a simple equation, but we have shown that the correlation followed a quadric equation (1,50,58).…”
Section: Estimation Of Daily •Oh Radical Scavenging Capacity Of Crn Imentioning
confidence: 84%
“…Thus, the serum CTL level and the CTL/Cr molar ratio are also reported to be good biomarkers of hydroxyl radicals. [10][11][12][13] Theoretically, the molar sum, CTL+MG, and its ratio to Cr, (CTL+MG)/Cr, may be the best indices for the precise hydroxyl radical level in vivo.…”
Section: Introductionmentioning
confidence: 99%